Clinical Characteristics, Outcomes, and Risk Factors of Disease Severity in Patients With COVID-19 and With a History of Cerebrovascular Disease in Wuhan, China: A Retrospective Study - Li, Mengzhen; He, Zehui; Yang, Jiecong; Guo, Qihua; Weng, Heng; Luo, Jielian; Gong, Baoying; Cui, Wanzhen; Ding, Banghan; Guo, Jianwen (Frontiers in Neurology, 2022)
Background and purpose: Coronavirus disease 2019 (COVID-19) rapidly resulted in a pandemic. People with cerebrovascular disease (CVD) are often related to severe infections. This study investigated the clinical features and risk factors of developing adverse outcomes in COVID-19 patients with a history of cerebrovascular disease (CVD). Method: This was a single-center retrospective clinical study including all the confirmed cases of COVID-19 at Wuhan Huoshenshan Hospital from Feb 4, 2020, to Apr 7, 2020. Differences in clinical characteristics were compared between patients with and without a history of CVD. The incidence of severe events comprised of all-cause death, intensive care unit admission, shock, or mechanical ventilation during hospitalization between two groups was compared using propensity score matching analysis and multivariate logistic regression analyses. Besides, the risk factors of developing severe events in COVID-19 patients with a history of CVD were analyzed. Results: A total of 2554 consecutive patients were included in our study, of whom 109 (4.27%) had a medical history of CVD. Patients with CVD tend to be older with more comorbidities, including hypertension, diabetes, coronary heart disease, and chronic obstructive pulmonary disease. The levels of white blood cell, neutrophil, C-reaction protein, creatine kinase isoenzymes, and lactate dehydrogenase were higher, whereas the levels of lymphocyte and albumin were lower in the CVD group. Compared to non-CVD patients, CVD patients were more likely to have severe events after age matching (12.8% versus 5.7%, P=0.012). After adjusting for the confounding effects of age, sex, smoking, and comorbidities, the odds ratio for developing severe events in the CVD group compared to the non-CVD group was 2.326 (95% CI, 1.168-4.630; P=0.016). Besides, CVD patients with decreased lymphocyte count (OR 9.192, 95% CI, 1.410-59.902, P=0.020) or increased blood urea nitrogen (OR 5.916, 95% CI, 1.072-32.641, P=0.041) had a higher risk of developing severe events during hospitalization. Conclusion: Patients with a history of CVD tend to have adverse clinical outcomes after being infected with SARS-COV-2. Decreased lymphocyte counts and increased blood urea nitrogen levels may be the risk factors for adverse outcomes in COVID-19 patients with previous CVD.